Formulasi Mouthwash Ekstrak Kulit Buah Nanas (Ananas comosus (L.) Merr) dengan Variasi Konsentrasi Gliserin sebagai Antibakteri Terhadap Streptococcus mutans ATCC 25175 - Maharani, Novita; Aisiyah, Siti; Purwaningsih, Desi (Jurnal Farmasi (Journal of Pharmacy), 2021)
Dental caries is a major disease in problems in the oral cavity especially in the teeth. The main cause of dental caries is the bacterium Streptococcus mutans which is a normal inhabitant of the oral cavity. Dental caries can be overcome using a mouthwash preparation containing antibacterial substances. Pineapple skin (Ananas comosus (L.) Merr) is one of the plants that contains substances that have antibacterial activity. The purpose of this study was to determine the physical quality and stability, and activity antibacterial of mouthwash pineapple skin extract. Pineapple skin extract was made in three mouthwash formulations using various concentrations of glycerin 5%, 10%, and 15%. Mouthwash were tested for physical quality and stability. Antibacterial activity test against Streptococcus mutans ATCC 25175 using the well method. The data obtained are presented in the form of tables and graphs processed with SPSS ver22 with the Paired T-Test method for testing viscosity and testing pH and ANOVA for measuring the diameter of the inhibition zone. The results showed that mouthwash preparations in all formulas with organoleptic physical qualities, viscosity, and stability produced good preparations, while in testing the physical quality of the pH did not meet the pH requirements of mouthwash preparations because of the influence of pineapple skin extract (Ananas comosus (L.) Merr). In testing the antibacterial activity of mouthwash, the diameter of the inhibition zone was obtained the base 0 mm; F1 11.08 mm; F2 13.08 mm; F3 15.08 mm; and control positive 16,75 mm.